Digital meets smart: towards a technology-enhanced approach to Smart Specialisation Strategy development. Issue 9 (2nd September 2022) - Mora, Luca; Panori, Anastasia; Deakin, Mark; Ortega-Argiles, Raquel
ABSTRACT: Conceived in the framework of regional studies on Smart Specialisation Strategy (S3) development, this special issue strengthens research efforts oriented towards assembling a technology-enhanced approach to S3 policymaking. First, it sheds light on fundamental methodological limitations that affect S3 development and reports on the digital support tools currently available. Second, it offers a knowledge base for producing novel digital applications that align with the overlooked needs of S3 orchestrators. Third, it complements this practical input with theoretical advancements in regional innovation studies by addressing intellectual questions and policy issues of pivotal importance for the S3 debate.